Pengaruh Game Online Terhadap minat Siswa Belajar PAI Pada Kelas IX di SMP 6 Pasaman Barat - Siti Fatimah Usmar; Irna Andriati (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This research was motivated by events that occurred in the field, that since Covid-19 the learning process was shifted to online or online learning at SMP N 6 Pasaman Barat. The learning process only uses mobile phones as a communication tool. Because students learn to use cellphones besides studying, they also participate in online games a lot. Based on initial observations, it appears that grade IX students are addicted to playing online games so that interest in learning PAI tends to decrease, often neglects PAI assignments and sometimes prefers to skip school. Therefore, this study aims to determine how much influence online games have on students' interest in learning PAI in class IX at SMP N 6 Pasaman Barat. The approach in this study is a quantitative type of correlation research. In this study, the population of class IX was 133 students, with a sample of 25%, namely 35 students, the sampling technique in this study used the Cluster Random Sampling method. The data collection technique is in the form of a questionnaire. The data processing technique uses the formula r product moment, correlation coefficient and coefficient of determination. Testing the data using normality test and linearity test.